Anticipated productivity and the labor market - Ryan Chahrour; Sanjay K. Chugh; Tristan Potter (Quantitative Economics, 2023)
We identify the main shock driving fluctuations in long-horizon productivity expectations, consistent with theories of TFP news. The identified shock induces strong comovement patterns in output, consumption, investment, employment, and stock prices even though TFP does not change significantly for more than 2 years. A labor search model in which wages are determined by a cash-flow sharing rule, rather than the present value of match surplus, matches the observed responses to the news shock. The model also matches the empirical patterns of vacancies, labor force participation, hours, and job-finding rates. The proposed wage rule is consistent with empirical responses of wages to both anticipated and unanticipated productivity changes.
Keywords: E24; E32; 330; News shocks; wages; labor search; business cycles